Immunogenicity and safety of zoster vaccine live administered with quadrivalent influenza virus vaccine. Issue 1 (2nd January 2018) - Levin, Myron J.; Buchwald, Ulrike K.; Gardner, Julie; Martin, Jason; Stek, Jon E.; Brown, Elizabeth; Popmihajlov, Zoran
Highlights: Zoster vaccine (ZV) given with quadrivalent inactivated influenza vaccine (IIV4). Concomitant/sequential GMTs of VZV gpELISA antibody responses were comparable. Concomitant/sequential GMTs of influenza HAI antibody responses were comparable. ZV administered concomitantly with IIV4 is generally well tolerated. Abstract: Objectives: Randomized, blinded, placebo-controlled trial to evaluate the safety and immunogenicity of ZOSTAVAX™ (ZV) administered concomitantly with quadrivalent inactivated influenza vaccine (IIV4) in adults ≥ 50 years of age (NCT02519855). Methods: Overall, 440 participants were randomized into the Concomitant Group (CG) and 442 into the Sequential Group (SG). The CG received ZV and IIV4 at separate injection sites on Day 1 and matching placebo at Week 4. The SG received placebo and IIV4 (2015–2016 influenza season) at separate injection sites on Day 1 and ZV at Week 4. Immunogenicity endpoints: Varicella-zoster virus (VZV) antibody geometric mean titer (GMT) and geometric mean fold-rise (GMFR) from baseline to 4 weeks postvaccination, measured by glycoprotein enzyme-linked immunosorbent assay (gpELISA) and adjusted for age and prevaccination titer. Influenza strain-specific GMT at baseline and 4 weeks postvaccination was measured by hemagglutination inhibition (HAI) assay. Safety endpoints: Injection-site and systemic adverse experiences (AEs) within 28 days following any vaccination and serious AEs throughout the study. Results: The adjusted VZV antibody GMT ratio (CG/SG) was 0.87 (95%CI: 0.80, 0.95), meeting the prespecified noninferiority criterion. The VZV antibody GMFR in the CG was 1.9 (95%CI: 1.76, 2.05), meeting the acceptability criterion. Influenza antibody GMT ratios for A/H1N1, A/H3N2, B/Yamagata and B/Victoria were 1.02 (95%CI: 0.88, 1.18), 1.10 (95%CI: 0.94, 1.29), 1.00 (95%CI: 0.88, 1.14), and 0.99 (95%CI: 0.87, 1.13), respectively. The frequency of vaccine-related injection-site and systemic AEs was comparable between groups. No vaccine-related serious AE was observed. Conclusion: The concomitant administration of ZV and IIV4 to adults ≥ 50 years of age induced VZV-specific and influenza-specific antibody responses that were comparable to those following administration of either vaccine alone, and was generally well tolerated.